MODEL PEMBERDAYAAN ZAKAT PRODUKTIF: DAMPAK PROGRAM GEROBAK USAHA TERHADAP KESEJAHTERAAN MUSTAHIK - Siti Anisah Mutakaruma (Indonesia Journal of Zakat and Waqf, 2025)
This study examines the empowerment program of business carts managed by BAZNAS Palangka Raya aimed at improving the income and welfare of mustahik. The program is conducted through stages including socialization, data collection, verification, recipient determination, aid distribution, and monitoring and evaluation. The research uses a qualitative approach with observation, interviews, and documentation techniques. Results show the program positively impacts mustahik with significant income increases. Daily income rose from Rp 50,000–300,000 to Rp 150,000–400,000, depending on business type and location. Besides economic improvement, the program enhances mustahik’s confidence and social independence. Challenges include limited monitoring and marketing difficulties. Hence, strengthening mentoring, entrepreneurial training, and access to marketing and further financing are necessary for sustainable and optimized empowerment. The program serves as an effective model of productive zakat empowerment to alleviate micro-poverty in Palangka Raya